THEORETICAL CONCEPTS OF THE COMPETENCY-BASED APPROACH IN PHARMACEUTICAL EDUCATION - Reva, Tatyana (Continuing Professional Education: Theory and Practice, 2019)
This article provides the theoretical and methodological discourse of the competency-based approach in pharmaceutical education; it substantiates that “competence” is key central concept of the competency-based approach in pharmaceutical education, because, firstly, it combines knowledge and activity components of professionalism-related medical education; secondly, the notion of “competence” reflects the core content of pharmaceutical education – the result of (a person’s ability to successfully carry out his/her professional activities);thirdly, the concept of “competence” is integrative and yet dynamic in its nature, because it contains a number of similar or related aspects of knowledge and skills belonging to the sphere of public health in its broadest sense; it specifies the concept of “professional competence of a specialist in the pharmaceutical industry” regarding it as a dynamic combination of knowledge, skills, ways of thinking, attitudes and values, and other personal qualities that determine the ability of a specialist in the pharmaceutical industry to successfully carry out professional and / or educational activities on the issues concerning public health ;it specifies and substantiates the basic theoretical concepts of the competency-based approach in pharmaceutical education: 1) taking into account the fact that the leading factor of the organization of educational process in a medical higher educational institution is recognition of the student as a carrier of subjective experience, in the context of which the student perceives any training and educational influences;2) creating an integrated learning environment in the medical higher educational institution, in which the expected by community preparedness of the future specialist in the pharmaceutical industry (theoretical, practical, psychological, personal, etc.) would form in order to operate in the field of healthcare of the nation;3) individualization of the path of establishment and development of professional competence of a pharmacist-professional.